The association between physical activity, low-grade inflammation, and labour market attachment among people with multimorbidity: A cross-sectional study from the Lolland-Falster Health Study, Denmark - Vivian Rueskov Poulsen; Linda Kjær Fischer; Mette Aadahl; Ole Steen Mortensen; Søren T Skou; Lars Bo Jørgensen; Randi Jepsen; Anne Møller; Therese Lockenwitz Petersen; Jan Christian Brønd; Lars Tang; Mette Korshøj (Journal of Multimorbidity and Comorbidity)
Aim Evidence suggests low-grade inflammation (LGI) to be associated with multimorbidity. Furthermore, there are links between inflammation markers, physical activity (PA), and labour market participation. The aims of this study were to examine the association between PA and LGI in people with multimorbidity and if this association was moderated by self-reported labour market attachment. Methods Cross-sectional data were collected in the Lolland-Falster Health Study (LOFUS) from 2016–2020. We included 1,106 participants with multimorbidity and valid accelerometer data. PA was measured as the average counts per minute (CPM) per day during wake time and split in time spent in moderate to vigorous intensity (MVPA) and light intensity (LPA). Degree of inflammation was determined by high sensitive C-reactive protein (hsCRP) level. Associations were investigated using multiple logistic regression analyses, stratified by labour market attachment. Results The odds of having LGI was higher with lower amount of daily LPA. The highest odds of LGI was observed for CPM < 200 per day (odds ratio (OR) 2.55; 95% confidence interval (CI) 1.46–4.43), MVPA < 15 minutes per day (OR 2.97; 95 % CI 1.56–5.62), and LPA < 90 (OR 2.89; 95 % CI 1.43–5.81) with the reference groups being CPM ≥ 400 per day, MVPA ≥ 30, and LPA ≥ 180 min per day, respectively. We could not preclude an interaction between LPA and labour market attachment ( p = 0.109). Conclusion PA recommendations should be developed with attention to people with chronic diseases, who may experience barriers to reach PA at high intensities. People with no labour market attachment may benefit from primary and secondary prevention of multimorbidity.